التخلق بالزعفران في مصر في عصر سلاطين المماليك "648-923 هـ. = 1250-1517 م." - حماد، محمد جمال (جامعة قناة السويس - كلية السياحة والفنادق, 2021)
يمكننا أن ننظر إلى المسار التاريخي لأية حضارة من الحضارات باعتباره صيرورة تدريجية لانتقال أنماط العيش من البساطة وقضاء الضرورات إلى التعقيد وتنوع المتطلبات، وقد كانت الحضارة المصرية، بحكم أسبقيتها التاريخية، ذات سبق مميز في التقاط كل مادة من مواد الطبيعة تسهم في تحقيق الغنى الطقسي، حيث كانت الممارسات الطقسية من أهم ما ميز الحضارة المصرية على مدار تاريخ مناشطها الاجتماعية والدينية، وتجلت صورها في العصر الإسلامي خاصة في الحقبة المملوكية، وفي زمن مبكر انتقلت أنماط التواصل الجمعي من مستوى السعي لتوفير "ضرورات" العيش إلى مستوى الحرص على تحقيق "تحسينات" الحياة، سوف يكون مدخلنا لمعاينة جانب من جوانب هذا الشغف بالطقوس وتحقيق التحسينات هو رصد صفحات من التاريخ المصري في التخلق بالزعفران في مختلف المناسبات في العصر المملوكي. ويمكن أن نرصد ملاحظة أولية تشير إلى أن التخلق بالزعفران كان طقسا يتم في مواقف اجتماعية متباينة في طبيعة مكونها الانفعالي ومتفاوتة في طبيعة أثرها النفسي، كما اخترق سلوك التخلق بالزعفران مجمل طبقات المجتمع المصري فقد مارسه الحكام كما قام به أعضاء القاعدة العريضة من الشعب المصري أو عامة الناس. وتتمحور الدراسة الحالية حول تلك الحقبة التاريخية، مع البدء بالتعريف اللغوي والاصطلاحي للتخلق بالزعفران، يليه توضيح الاستخدامات المتنوعة لنبات الزعفران. كذلك بعض الإشارات التي توضح أسبقية الحضارة المصرية القديمة لممارسة طقس التخلق بالزعفران حتى قيام الدولة المملوكية، التي صار التخلق فيها علما بارزا تتنوع صوره فيها بين طبقات المجتمع في مختلف المواقف التي تعبر أحيانا عن الفرح والسرور، وأحيانا إظهار الشماتة، كما رصدت المصادر صور لتخليق الرسائل، والرايات، والملابس، والأكفان، والمنشآت المعمارية الدينية والمدنية بالزعفران.
When we look at the historical trajectory of any civilization as a gradual process of moving patterns of life from simplicity and fulfillment of necessities to complexity and diversity of requirements. By virtue of the Egyptian civilization historical precedence, it had a distinguished precedent in capturing every material of nature that contributed to achieve ritual richness. Where ritual practices were one of the most important features of Egyptian civilization throughout the history of its social and religious activities, And manifested itself portrayed in the Islamic era, especially since the Mamluk era, At an early age, patterns of group communication moved from the level of seeking to provide the "necessities" of living to the level of concern for achieving "improvements" in life. Our gateway to examining an aspect of this passion for rituals and achieving improvements will be to observe pages of the Egyptian history of Perfuming saffron on various occasions in the Mamluk era . Through an initial observation which indicated that Perfuming saffron consider a ritual that took place in social situations differed in the nature of its emotional component and varied in the nature of it's psychological effect, the behavior of Perfuming saffron included all classes of Egyptian society, where rulers use it as well as members of the common Egyptian people. The current study revolves around that historical period, with the beginning of the linguistic and idiomatic definition of Perfuming saffron, followed by an explanation of the various uses of the saffron plant. There are also some references that explain the precedence of the ancient Egyptian civilization to practice the ritual of perfuming saffron until the establishment of the Mamluk state, it became a prominent mark of the diversity of its images among the Strata of society in various situations that sometimes express joy and happiness, as well as show schadenfreude, the sources also mentioned pictures of the of perfuming messages, banners, clothing, shrouds, religious and civil architectural structures with saffron.
Keywords: العادات والطقوس -- الموروث الثقافي -- التاريخ الاجتماعي -- مصر -- العصر المملوكي